Some chemical and microbiological quality charactersitics of domestic goose (anser domesticus) meat - GürkanUçar Sait GürkanUçar; Ümit Gürbüz; Ahmet Güner; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
This study was done to determine some microbiological and chemical quality charactensties of goose meat. In this investigation, nine lemale and nine male geese were used. Mean moisture, protein, fat and ash content ol geese carcasses were found 61.54 %, 27,21 %, 10.60 % and 0.65 % respectively. Total mesophilic aerobic and psychrophilic aerobic microorganisms numbers were determined as 7 8x103 cpu/cm2 and 5.9x1ü2 cpu/cm2. on the other hand Salmonella. Staphylococcus-Micrococcus and yeast - mould were not seen.